The Building of an Epistemological Paradigm: Integration of the Qur'an and Hadith as the Foundation of Contemporary Islamic Knowledge - Mukhtar, Dertha; Charles, Charles; Rahma, Rifka Haida (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study discusses Islamic epistemology with a focus on the integration between revelation and rationality in the construction of knowledge. The main objective of this research is to examine the position of the Qur’an as the primary (primordial) source within the Islamic epistemological system, the role of Hadith as its explanatory component, and how their methodological integration forms a holistic and non-dichotomous structure of knowledge. This research employs a qualitative approach through a literature review, analyzing both classical and contemporary works such as those of Al-Ghazali, Imam al-Shafi‘i, M. Abid al-Jabiri, Fazlur Rahman, and Syed Muhammad Naquib al-Attas. The findings indicate that the Qur’an possesses the highest epistemological authority as the ultimate source of truth, while Hadith functions as a practical interpretation that actualizes the Qur’anic values in daily life. Epistemological integration requires a methodological hierarchy in which revelation serves as the central axis, and reason acts as an instrument for contextual understanding and conceptualization. Knowledge in Islam is not dichotomous, as in Western traditions, but rather integrates the spiritual and rational, ethical and empirical dimensions. In conclusion, Islamic epistemology constructs a holistic knowledge system grounded in revelation as the source of values and truth, with reason as a tool for interpretation. This model enables the development of knowledge that is spiritually meaningful, socially relevant, and firmly rooted in divine values.